View of the Banganga Tank from the Parashuram temple - Banganga by Ghosh, Ayan (2023)
Hindu pilgrims perform parikrama (circumambulation) in a circular direction along a path going around Banganga Tank, starting from the south end. The important temples are located on the parikrama. The ghats have spatial division according to specific rituals; south and west are used for rituals of the dead and north and east are used for auspicious rites.